CULTURE OF PATIENT SAFETY IN THE HOSPITAL SETTING: AN INTEGRATIVE REVIEW. - Meneghetti Baratto, Mari Angela; Sebben Pasa, Thiana; Sbeghen Cervo, Anamarta; de Lima Dalmolin, Graziele; Pinheiro Pedro, Cecília Mariane; Bosi de Souza Magnago, Tânia Solange (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2016)
Objective: to identify productions related to patient safety and organizational culture, which used as data collection instrument the Safety Attitudes Questionnaire. Method: an integrative review, in the databases LILACS, MEDLINE/PubMed, Scopus and Web of Science, with patient safety descriptors, organizational culture, climate, attitude of health personnel and the keyword safety attitudes questionnaire, with articles published online, in full, by the year 2013. Results: we obtained 16 publications for analysis and discussion, presented in two categories. The studies used as subjects health professionals. The inclusion of other professionals was not sufficiently covered, but represents an important role in creating safe work environments. An association of organizational culture with safety environment for the professionals was verified. Conclusion: it is believed that this study will bring contributions to the health team, especially to nursing, regarding the implementation of improvement actions in health institutions.